2001
DOI: 10.1021/jp0105488
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Biocompatible Water-Soluble Silica-Coated CdSe/ZnS Semiconductor Quantum Dots

Abstract: We describe the synthesis of water-soluble semiconductor nanoparticles, and discuss and characterize their properties. Hydrophobic CdSe/ZnS core/shell nanocrystals with a core size between 2 and 5 nm are embedded in a siloxane shell and functionalized with thiol and/or amine groups. Structural characterization by AFM indicates that the siloxane shell is 1-5 nm thick yielding final particle sizes of 6-17 nm, depending on the initial CdSe core size. The silica coating does not significantly modify the optical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
957
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 1,238 publications
(982 citation statements)
references
References 34 publications
19
957
0
6
Order By: Relevance
“…In the first report of silica shell growth around CdSe/ZnS QDs, it was suggested that the silica shell thickness around 4 nm nanocrystals was 1-2 nm, while its thickness around 6-7 nm QDs was 3-4 nm. 6 This interpretation is consistent with further fluorescence correlation spectroscopy (FCS) measurements that indicate that the hydrodynamic radius of silanized CdSe/ZnS QDs is dependent on the initial size of the underlying quantum dots. The same trend could be observed in the case of CdTe quantum dots.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the first report of silica shell growth around CdSe/ZnS QDs, it was suggested that the silica shell thickness around 4 nm nanocrystals was 1-2 nm, while its thickness around 6-7 nm QDs was 3-4 nm. 6 This interpretation is consistent with further fluorescence correlation spectroscopy (FCS) measurements that indicate that the hydrodynamic radius of silanized CdSe/ZnS QDs is dependent on the initial size of the underlying quantum dots. The same trend could be observed in the case of CdTe quantum dots.…”
Section: Discussionsupporting
confidence: 83%
“…Gradual quenching of the silanized nanoparticles was observed while silanized CdSe/ZnS synthesized by known literature methods were the control. 6 Bioconjugates in that particular gel were of thin-shelled CdTe QDs and had not been subjected to ethanol precipitation. The quenching was highly reproducible from silanized sample to sample and showed the need to thicken the silica shell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 While the core/shell Qdots are only ~4-5 nm in size, the silane shell adds 2-3 nm in thickness and thus silanized Qdots are ~8-10 nm in diameter. 29 Such Qdot chemistry was observed to pose minimal toxicity to breast cancer cells when the cells were exposed to a solution containing 2-10 nM of PEG-silane-Qdots. 26 Human lung (IMR-90) and skin epithelial (HSF-42) cells were exposed for 48 h to a medium containing 8 or 80 nM Qdots or to an equivalent amount of 10 mM phosphate buffer as a control.…”
Section: Methodsmentioning
confidence: 99%
“…This was dissolved in 50 mm 3 of 3-mercaptopropyltrimethoxysilane (MPTS) to modify the surface of CdSe nanoparticles (MPTS/ CdSe), where thiol groups of MPTS molecules were strongly bound to Cd 2+ sites of nanoparticles. 15 A colloidal solution of water-soluble SiO 2 -coated CdSe nanoparticles (SiO 2 /CdSe (col)) was prepared from MPTS/CdSe by using the same method as that reported by Alivisatos and co-workers, 5 with the outermost layer being prepared through the condensation of surface hydroxyl groups on the SiO 2 shell with (trihydroxysilyl)propyl methylphosphonate (TSPP) and hydrolysis ( Figure S1a in the Supporting Information). The resulting nanoparticles were dissolved in an aqueous solution and purified by dialysis.…”
Section: Methodsmentioning
confidence: 99%